Agua que aún mueve molino: aproximación a la historia balnearia - Rodríguez Sánchez, Juan Antonio (Anales de Hidrología Médica, 2008)
The complexity of the balneology phenomenon demands a historical analysis which considers the diverse human groups, formed around mineral waters (bathers, owners and scientists), their relationships with water (use, exploitation and study) and the relationships among them in the framework of thermal establishment. It is therefore important to consider some other different determining factors, such as the location where the spa is settled down, the general attitudes which science has towards cure by water and the valuation which society has made from water in every point in history.